Whitman among the Bohemians - Levin, Joanna; Whitley, Edward Keyes (Iowa Whitman series., 2014)
For several years just before and just after his 1860 edition of Leaves of Grass appeared, Walt Whitman regularly frequented Pfaff's beer cellar in downtown Manhattan. The basement bar was the very center of mid-nineteenth-century American bohemian activity and was heavily patronized by writers, artists, musicians, actors, intellectuals, and radicals such as free-love advocate Henry Clapp, Jr., and Broadway succès de scandale Adah Isaacs Menken. Numerous creative and political ventures emerged from this environment, and at least two bohemian literary weeklies, The New-York Saturday Press and Vanity Fair, shared origins around the tables at Pfaff's. In this milieu, Whitman found sympathetic supporters of his poetic vision, professional connections, rivals, romantic partners, and close friends, and left a lasting impression on poet and critic Edmund Clarence Stedman, an erstwhile bohemian who later in the century emerged as a tastemaker of American poetry. Yet for many years, the bohemians associated with Pfaff's have served merely as minor background characters in Whitman scholarship. Whitman among the Bohemians corrects that by exploring in depth the connections Whitman made at Pfaff's and the impact they had on him, his poetry, and his career. In telling the story of these intersecting social and professional links that converged at Pfaff's in the late 1850s and early 1860s, the essays in this volume powerfully demonstrate just how much we can learn about Whitman and his work by viewing him within the context of American bohemia. CONTRIBUTORS: Stephanie Blalock, Ruth Bohan, Leif Eckstrom, Logan Esdale, Amanda Gailey, Karen Karbiener, Joanna Levin, Mary Loeffelholz, Eliza Richards, Ingrid Satelmajer, Robert J. Scholnick, Edward Whitley.